Earned Value Management (EVM) dalam Estimasi Biaya Proyek Piranti Lunak Menggunakan Spiral Development - Adhi Kusnadi (Universitas Multimedia Nusantara, 2015)
The success of a project is determined by the success of a software team in estimating the budget plan the cost of the software. The purpose of this paper is the creation, devise ways to estimate project budget software. To be able to compose a Planned Value (PV) project software required several steps. The first step is the preparation of WBS. Division of phase-phase creation of software applications in this paper follow the steps in the development of the software spiral. The second step is a software metric, method is the most straightforward and easiest in its application is a measurement based on metric size oriented. Intentionally taken a sample project that contains the work of hardware, so that can be made analysis unit price for the item that has a high price and need analysis. A summary of which can be taken from this discussion is the preparation method of estimating budget projects have successfully made systematically. How is made as simple as possible so that the team members have no experience whatsoever can make a budget. Keywords: Planned Value (PV) method, spiral, WBS, budget.